Fostering Critical Thinking and Digital Literacy: Students’ Use of the Verb “Be” in English Sentences - Masbiran, Gunaldi; Fathira, Vina; Asril, Lelly Zuyana (ENGLISH JOURNAL OF INDRAGIRI, 2026)
This study aims to analyze students’ mastery of the verb be in various sentence forms and to evaluate the role of digital-based exercises in enhancing students’ critical thinking and digital literacy skills. The study employed a quantitative descriptive approach, with data collected through Google Forms from 12 EFL students. The research instrument consisted of multiple-choice questions, with 10 items each for positive sentences, negative sentences, and interrogative sentences. The results indicate that students are more proficient in forming positive sentences, while negative and interrogative sentences show higher error rates, particularly regarding subject-verb inversion and the use of not. Activities requiring students to explain their answer choices fostered the development of critical thinking skills, while the use of an online platform strengthened their digital literacy. The limitations of this study include a relatively small sample size and a focus on simple sentences. Future research is suggested to expand the sample, use more complex sentences, and explore the relationship between grammar mastery, critical thinking, and digital literacy in more authentic learning contexts.